СУГЕСТИВНІ ТЕХНОЛОГІЇ ЯК УМОВА ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛЯ МУЗИКИ (Педагогіка вищої та середньої школи, 2007)
In article application the suggestive technologies which promote successful mastering of the realized and not realized components of mentality during mastering a material is considered. Use auto-trainings, various kihtl.s of meditations for development of emotional - shaped sphere is offered.